Comparing macrophyte herbivory by introduced Louisiana crayfish (Procambarus clarkii) (Crustacea: Cambaridae) and native Dytiscid beetles (Cybister tripunctatus) (Coleoptera: Dytiscidae), in Kenya - Rosenthal, Sadie K.; Lodge, David M.; Mavuti, Kenneth M.; Muohi, Wairimu; Ochieng, Philip; Mungai, Benjamin N.; Mkoji, Gerald M. (My University, 2005)
The omnivorous Louisiana crayfish, Procambarus clarkii, has caused significant changes to macrophyte communities worldwide and may have similar negative effects in Kenya if used as a biological control agent for snails harbouring human schistosomes. Here we examine how herbivory by the introduced Louisiana crayfish might change macrophyte abundance and species composition relative to herbivory by a prevalent native beetle Cybister tripunctatus. Our observations are thought to be the first on the consumption of live macrophytes by adult dytiscid beetles, which are commonly known as predaceous diving beetles. In a laboratory experiment, we compare herbivory rates and macrophyte species-selectivity between the beetle and the crayfish. Combining the herbivory rates with population estimates of crayfish and beetles in a local pond, we estimate that herbivory in the natural environment is of the same order of magnitude. Preferences among macrophyte species are also similar between herbivores, except that crayfish are likely to have a larger impact than beetles on cultivated rice (Oryza sativa). Results from a laboratory toxicity experiment suggest that the crayfish is not currently a rice pest in Kenya because it is killed by Furadan® 5G, the commonly applied pesticide.